Antibacterial activities in various tissues of the horse mussel, Modiolus modiolus - Haug, Tor; Stensvåg, Klara; Olsen, Ørjan M.; Sandsdalen, Erling; Styrvold, Olaf B. (Journal of Invertebrate Pathology, 2004)
A search for antibacterial activity in different organs/tissues of the horse mussel, Modiolus modiolus, was conducted. Dried samples were extracted with 60% (v/v) acetonitrile, containing 0.1% (v/v) trifluoroacetic acid. Due to high salt content, two liquid phases were obtained; an acetonitrile-rich phase (ACN extract) and an aqueous phase. The aqueous phase was further subjected to solid phase extraction (SPE). Eluates from SPE and ACN extracts were tested for antibacterial, lysozyme, and toxic activity. Antibacterial activity was demonstrated in extracts from several tissues, including plasma, haemocytes, labial palps, byssus, mantle, and gills. Some of the extracts were sensitive to proteinase K treatment, indicating antibacterial peptides and/or proteins. Lysozyme-like activity and toxic activity against Artemia salina nauplii was detected in fractions from the gills, mantle, muscle, and haemocytes. Results from this study indicate that M. modiolus is a promising source for identifying novel drug lead compounds.